Case series of retained rectal foreign body. A Malaysian experience. - Pang Wei Soon (Academy of Family Physicians of Malaysia, 2021)
Retained rectal foreign body, with its associated social stigma, is a medical condition that is infrequently reported in Malaysia. We report the surgical management of five cases of retained foreign objects in the rectum seen over a one-year period. There were three young and two elderly male patients. One of the elderly patients presented with altered bowel habits and an abdominal mass that mimicked a symptomatic colonic tumor. All patients had an abdominal radiograph which clinched the diagnosis of a retained foreign rectal body. Successfully retrieved objects included two bottles, one bidet device, and two sex toys. Open surgery for retrieval of the impacted rectal foreign body was required in one patient. All underwent successful retrievals without any adverse postoperative complications. In our case series, retained rectal foreign bodies were observed only in the male gender. The age presentation was bimodal, with age groups in the twenties and sixties. The treatment options used for the retrieval of these impacted foreign bodies included transanal extraction or explorative laparotomy. Proximal migration and delayed presentation are possible indications for the latter approach.